2020
DOI: 10.1249/mss.0000000000002372
|View full text |Cite
|
Sign up to set email alerts
|

The Menopause Alters Aerobic Adaptations to High-Intensity Interval Training

Abstract: Introduction: Post-menopausal women have lower resting cardiac function than premenopausal women, but whether the menopause influences maximal cardiac output and hence exercise capacity is unclear. It is possible that pre-and post-menopausal women achieve similar improvements in peak aerobic capacity (V O 2peak ) and cardiac output with exercise training via different regional left ventricular muscle function ("LV mechanics"), as suggested by in vitro and animal studies. The aim of this study was to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…The importance of regional LV deformation, at the LV apex, was again highlighted. Several other studies have revealed similar patterns of LV twist during exercise in pre-and postmenopausal women, in athletes and of humans ascending to high altitude [58][59][60][61][62]. Consequently, it is now generally accepted that an increase in LV twist with exercise up to moderate intensities can be expected as a normal response (Figure 3).…”
Section: Physiological Insight From Healthy Individualsmentioning
confidence: 72%
See 1 more Smart Citation
“…The importance of regional LV deformation, at the LV apex, was again highlighted. Several other studies have revealed similar patterns of LV twist during exercise in pre-and postmenopausal women, in athletes and of humans ascending to high altitude [58][59][60][61][62]. Consequently, it is now generally accepted that an increase in LV twist with exercise up to moderate intensities can be expected as a normal response (Figure 3).…”
Section: Physiological Insight From Healthy Individualsmentioning
confidence: 72%
“…In this regard, Burns et al showed that aging seems to be associated with a reduced LV twist reserve during exercise in a population of 60-year old individuals [66]. Similarly, "female aging", as represented by the menopause, seems to impact the myocardial response to exercise, which may be further altered by exercise training [58]. One of the more surprising observations has been that of Cooke et al who proposed that endurance trained athletes with enlarged "athlete's heart" and a greater stroke volume had a similar systolic LV function, including LV twist, during submaximal exercise compared to untrained humans with smaller stroke volume [67].…”
Section: Physiological Insight From Healthy Individualsmentioning
confidence: 99%
“…A recent meta-analysis of 26 studies (n = 468 healthy individuals) found similar LV hypertrophy adaptations to endurance training among men and women, but that LV end-diastolic, end-systolic and stroke volumes increased more in men (31). In addition, women appear to experience greater improvements in arteriovenous oxygen difference with endurance training compared to men (32)(33)(34). The sex differences literature on exercise training responses is primarily limited to healthy adults, as the studies of patients with heart failure have been predominantly performed in men (35).…”
Section: Influence Of Sex and Age On The Effects Of Exercise Training...mentioning
confidence: 99%
“…In younger, premenopausal women, the adaptations to endurance training are more likely related to peripheral determinants as opposed to LV adaptations, as seen in men ( 27 , 36 , 40 , 41 ). Older, post-menopausal women experience similar peripheral adaptations to endurance training but appear to have a smaller increase in peak VO2 and blood volume compared to premenopausal women ( 32 ). Spina et al demonstrated that among older (60–70 years) women, 9–12 months of endurance training increased peak VO 2 and arteriovenous oxygen difference, but LV end-diastolic and stroke volumes did not change ( 40 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation